Community-based intervention improves abortion knowledge and reduces abortion stigma among women in Oromia, Ethiopia: a quasi-experimental mixed methods evaluation - Bekalu Mossie Chekol; Sally Dijkerman; Samuel Muluye; Dereje Wondimu (BMC Women's Health, 2022)
Abstract Background Since liberalization of the Ethiopian abortion law, there have been significant improvements in the availability and utilization of facility-based abortion services in the country. However, nearly half of abortions still take place outside of health facilities, where the quality of procedures remains unknown. Abortion stigma is one reason that unsafe abortion persists. This study aims to evaluate the effect of community interventions conducted from 2016 to 2019 on the level and manifestation of abortion stigma and knowledge in a community in Oromia region, Ethiopia. Methods The study is a quasi-experimental mixed methods evaluation including intervention and comparison communities. Two cross-sectional structured household surveys with independent samples, participatory evaluation wheels, and participatory impact diagrams were conducted with women of reproductive age (15–49) living in the communities. The baseline was conducted in 2016 and the endline in 2019. Difference-in-differences analysis was used to estimate the effect of the intervention on abortion knowledge and Stigmatizing Attitudes, Beliefs, and Actions Scale (SABAS) scores in the intervention community. Results One thousand five hundred fifty-five women participated in the household survey and 28 women participated in participatory evaluation meetings. Over one-third (37%) of women surveyed in the intervention community were exposed to the intervention activities. Knowledge of one or more indications of legal abortion increased from 21 to 85% in the intervention community, compared to an increase from 30 to 57% in the comparison. Mean SABAS scores decreased by 9.3 points in the intervention community and increased by 5.3 points in the comparison community. Differences-in-differences models indicate that exposure to the intervention resulted in decreased stigma scores (coefficient = − 9.33, p < 0.001) and increased knowledge (coefficient = 0.26, p < 0.001). Conclusions This is one of the first studies to measure changes in community-level abortion stigma and knowledge over time in Ethiopia using a mixed method, quasi-experimental design. The results indicate that the community-based intervention improved abortion knowledge and reduced abortion stigma.